Pengaruh Ukuran Dewan Komisaris, Gender Diversity pada Dewan, dan Kualitas Auditor Eksternal terhadap Agresivitas Pajak (Studi pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Desi Ambarsari; Dudi Pratomo; Kurnia Kurnia (Kompartemen : Jurnal Ilmiah Akuntansi, 2019)
This study aims to analyze board of commissioner size, gender diversity in boards, external auditor quality, and tax aggressiveness on property and real estate sector companies listed in Indonesia Stock Exchange (IDX) in the period of 2013-2017. In addition, to analyze the effect simultaneously and partially between board of commissioner size, gender diversity in boards, and external auditor quality against tax aggressiveness in property and real estate sector companies listed in Indonesia Stock Exchange (IDX) in the period of 2013-2017.The analytical method used is descriptive statistical test and panel data regression analysis using Eviews version 10. The technique of selecting the sample used is purposive sampling and obtained 28 property and real estate companies with a period of research for five years in 2013-2017 so obtained 140 units sample in this research.The results of this study also show that simultaneously the Board of Commissioners Size, Gender Diversity on the Board, and the Quality of External Auditors influence Tax Aggressiveness in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2017 period. Partially Gender Diversity on the Board has a negative effect on Tax Aggressiveness, while Board of Commissioners Size and External Auditor Quality have no effect.Keywords: Tax Aggressiveness, Board of Commissioner Size, Gender Diversity in Boards, External Auditor Quality